KONTEKSTUALISASI MAKNA IBNU SABIL DALAM AL-QUR’AN DI ERA MODERN-KONTEMPORER - Kusroni Kusroni; Shiela Al-Maulidia; Mas'ud Abdillah (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
The premodern context places classical commentators on a single interpretation of the term ibn sabil in the Qur'an. They only interpret ibn sabil as a traveler (musafir) who has run out of supplies. This limited meaning can no longer be maintained, because the social, economic, and political context in the modern-contemporary era has changed. This research seeks to contextualize the verses of ibnu sabil in the Qur'an in the modern-contemporary era. This research is a qualitative type by utilizing library data collected through the maudhu'i method, with a focus on verses that offend ibn sabil. Meanwhile, Abdullah Saeed's contextual approach is used as an analytical tool. This research compiles eight verses about ibnu sabil in the Qur'an which are spread over seven surahs, consisting of two makkiyah surahs and six madaniyyah. The finding is that the verses of ibn sabil are included in the second hierarchy of values, namely fundamental values. Contextualization of ibn sabil's verses in the modern-contemporary era places ibn sabil in a broader meaning than just travelers, as in premodern interpretations. Ibnu sabil currently includes “anak jalanan” and those who do not have a permanent residence (homeless). Therefore, zakat management institutions, both from the private sector and the government, should be able to expand the scope of zakat recipients (mustahik) from the ibnu sabil cluster, as found in this study.